Law and Lawyers in a Divided World - Robert G. Storey (Washington University Law Quarterly, 1958)
Most people, including historians, are concerned almost exclusively with the forms and institutions of government and only incidentally with legal systems. Abrupt and radical changes in political power make headlines in the press. Professor Whitney R. Harris aptly described the condition when he said: "Legal systems by contrast are drab and technical, and when changes occur they are seldom recognized as having great significance.” Political systems rise and fall according to the vicissitudes of popular interest and the designs of ambitious men. However, the basic structure of established legal systems usually survives the most violent political storms.
Keywords: Administration of justice; Urban transportation – Federal aid; Attorneys; Soviet Union